Legal Requirements for Human-Health Based Appeals of Wind Energy Projects in Ontario - Engel, Albert M. (Frontiers in Public Health, 2014)
In 2009 the government of the province of Ontario, Canada passed new legislation to promote the development of renewable energy facilities, including wind energy facilities in the province. Throughout the legislative process, concerns were raised with respect to the effect of wind energy facilities on human health. Ultimately, the government established setbacks and sound level limits for wind energy facilities and provided Ontario residents with the right to appeal the approval of a wind energy facility on the ground that engaging in the facility in accordance with its approval will cause serious harm to human health. The first approval of a wind facility under the new legislation was issued in 2010 and since then, Ontario’s Environmental Review Tribunal as well as Ontario’s courts have been considering evidence proffered by appellants seeking revocation of approvals on the basis of serious harm to human health. To date, the evidence has been insufficient to support the revocation of a wind facility approval. This article reviews the legal basis for the dismissal of human-health based appeals.